PERENCANAAN GEOMETRI JALAN REL ANTARA TARAHAN BAKAUHENI - Sari, Nurwanda; Bustam, Hadyan Arifin; Setyaji, Arif; Pamursari, Nurmagita; Zhafari, Rizaldi (PendIPA Journal of Science Education, 2024)
As technology continues to advance and Indonesia's population experiences rapid growth, transportation is also progressing. The train is a mode of transportation designed to carry passengers and goods, whether in small or large quantities, over long distances. Trains are one efficient modes of land transportation. This research located along Tarahan Bakauheni route, with the shortest straight distance spanning 50 km. The data used for the design of this railway track includes Passenger Data from Bakauheni Port, Coal Cargo Data, Topography Data, and other supporting data. The planning phase is carried out using regulations such as Ministerial Regulation No. 60 of 2012, PD 10, and other relevant rules. In the railway design, used is Class I with a track gauge of 1067 mm. The Horizontal Alignment planning for the route involves 42 curves with the SCS type, where each curve has a radius of 850m, a track elevation of 79.023 mm, and a transition curve length of 94.828 m. Class I railway has a maximum ruling gradient of 10‰ and includes 18 vertical curves with a radius of 8000m. The structure of the railway uses R60 type rails with concrete sleepers and employs double elastic fasteners of the Pandrol Fastclip type.